Exactly solved models : a journey in statistical mechanics ; selected papers with commentaries (1963 - 2008) - 456136 Fa, Yueh Wu; Yang, Chen Ning, 1922-; Maillard, Jean-Marie (Hackensack, NJ : World Scientific Publishing Company, 2009)
Includes bibliographical references and index